Effects of a calorie restricted diet on the insulin-stimulated glucose uptake and content of lipids in skeletal muscle of 24-month-old rats - Бабенко, Н. О.; Мілько, О. С. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2013)
The aim of this work was to investigate the effect of calorie restricted diet (CRD) on insulin-stimulated glucose uptake and content of neutral lipids and phospholipids in soleus muscle (SM) and extensor digitorum longus (EDL) of 24-month-old rats. CRD increased the content of phosphatidylcholine and phosphatidylethanolamine and reduced the levels of free fatty acids, triacylglycerols, diacylglycerols and cholesterol in SM of rats. CRD increased the insulin-stimulated glucose uptake in EDL of experimental rats versus control group. Application of CRD resulted in modulation of insulin-stimulated glucose uptake in skeletal muscle of rats with parallel reduction of lipids involved in insulin signaling. The results obtained might indicate the protective role of CRD in age-related disorders of insulin signaling pathway.